2018
DOI: 10.3390/nu10111786
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone-Associated Dietary Pattern Predicts Low Testosterone Levels and Hypogonadism

Abstract: Obesity and low serum testosterone (T) levels are interrelated and strongly influenced by dietary factors, and their alteration entails a great risk of hypogonadism. Substantial evidence suggests a bidirectional relationship between nutrient metabolism (e.g., glucose, lipids, and iron) and T levels in men; however, T-related dietary patterns remain unclear. This study investigated the dietary patterns associated with serum total T levels and its predictive effect on hypogonadism and the body composition. Anthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 55 publications
0
43
0
Order By: Relevance
“…The current study found that >1 g of ferric iron suppressed serum and testicular total T levels; however, 2 g of iron had less severe effect due to high intra-individual group variations. The concentration of total T in the blood circulation can be influenced by age, diet, obesity, and the time at which blood is withdrawn [44][45][46]. Brambilla et al [47] suggested that intra-individual variations, and not assay variations, accounted for biological variations in the male sex hormone.…”
Section: Discussionmentioning
confidence: 99%
“…The current study found that >1 g of ferric iron suppressed serum and testicular total T levels; however, 2 g of iron had less severe effect due to high intra-individual group variations. The concentration of total T in the blood circulation can be influenced by age, diet, obesity, and the time at which blood is withdrawn [44][45][46]. Brambilla et al [47] suggested that intra-individual variations, and not assay variations, accounted for biological variations in the male sex hormone.…”
Section: Discussionmentioning
confidence: 99%
“…Limited published articles have investigated specific dietary patterns with male testosterone levels. A recent cross-sectional study in 125 Taiwanese men reported that higher adherence to a typical high-calorie Western diet was associated with decreased testosterone level by 0.87 ng/mL [38]. However, another study found that men consuming vegetarian diets had no association with serum testosterone levels [14, 15].…”
Section: Discussionmentioning
confidence: 99%
“…Our outcomes were also continuous measures without any known threshold that can be applied. Besides, most of the existing literature on the determinants of sex hormones have applied linear regression models to model the variation in the outcome [ 56 , 57 , 58 , 59 , 60 ]. The decision to use linear regression was also based on the fact that [ 61 , 62 , 63 ] mediational models are easier to operationalize when the mediators and the outcomes are continuous measures.…”
Section: Methodsmentioning
confidence: 99%